John Paul II’s Care for Seminaries. The Pope in Hosianum - Rabczyński, Paweł (Studia Warmińskie, 2011)
John Paul II’s care for seminaries falls within the implementation of the broadly understood teaching framework of the Second Vatican Council. In his numerous addresses and documents on the subject of becoming a priest the Pope reinterpreted the Council documents in a way which was attuned to modern times. He did this, since he wanted seminarians, who are educated to fulfill and continue the mission of Christ himself, to be properly prepared to take on the legacy and teachings of the Council in the third millennium of Christendom. John Paul II describes seminaries as educational collectivity “on the way” constituting a certain continuation of Christ’s disciples’ collectivity, whose experience determines the seminary’s identity and its normative ideal.